TEACHING LITERATURE WITH TOUGH TOPICS IN ELT CLASS: BULLYING AND BIGOTRY - Dewi, Novita (LLT Journal: A Journal on Language and Language Teaching, 2019)
Literature is an important vehicle to teach character building in language education. Sensitive topics like bullying and prejudice in literary works are helpful to promote understanding and empathy toward others. This article aims to discuss two short stories, namely “All Summer in a Day” by Ray Bradbury and “Shame” by Dick Gregory that can be used to increase students’ critical thinking, conscience, and compassion in language learning. The first half of the article examines the rationale for using short stories with such topics to impart values in language learning. The other half explores the significance of the two stories to use in ELT class. The article concludes that studying literature is, by default, practicing character education and that good support and reinforcement for that purpose can be done by addressing delicate issues that sometimes may appear harsh and unpleasant. DOI: doi.org/10.24071/llt.2019.220107